Unhealthy weight control behaviors among Ethiopian female adolescents. Issue 4 (16th January 2020) - Tuffa, Tigest A.; Gebreyesus, Seifu H.; Endris, Bilal S.; Getnet, Yalemwork; Abebe, Dawit S.
Abstract: Background: Unhealthy weight control behaviors are a serious concern, impairing the quality of life in adolescents. Although recent epidemiological studies indicate a high level of disordered eating in developing countries, such data in Ethiopia are scarce. Thus, this study aimed to determine the extent of unhealthy weight control behaviors (i.e., purging and nonpurging) and corresponding associated factors among urban Ethiopian adolescents. Method: A cross‐sectional study using self‐administered questionnaires was applied to 690 randomly selected female high school adolescents in Addis Ababa, Ethiopia in 2017. Measures included unhealthy weight control behaviors, body mass index, subjective perception of body weight, appearance satisfaction, depressive symptoms, and socio‐demographic factors. Logistic regression was applied for data analyses, that is, adjusted odds ratio (aOR) with 95% confidence interval (CI). Results: The level of unhealthy weight control behaviors (i.e., a score of at least once a week in the last 1 month) was 30.7% ( N = 208). Specifically, the extent of purging and nonpurging weight control behaviors was 1.5% ( N = 10) and 29.8% ( N = 202), respectively. Factors that were significantly associated with unhealthy weight control behaviors were perception of being overweight [aOR = 3.01; 95%CI: 1.11–8.11], being overweight [aOR = 3.28; 95%CI: 1.54–7.01], severe depression [aOR = 4.09; 95%CI: 1.73–9.96], and high socio‐economic status [aOR = 2.07; 95%CI: 1.30–2.80]. Conclusion: This study reveals a considerable level of unhealthy weight control behaviors among female adolescents in an urban setting in Ethiopia. Researchers and policy makers should focus their attention upon this emerging public health challenge and develop associated strategies.